Molecular cytological analysis of alien introgressions in common wheat lines created by crossing of Triticum aestivum with T. dicoccoides and T. dicoccum - О. A. Orlovskaya; I. N. Leonova; L. A. Solovey; N. I. Dubovets (Вавиловский журнал генетики и селекции, 2023)
Wild and domesticated emmer (ВВАА, 2n = 28) are of significant interest for expanding the genetic diversity of common wheat as sources of a high protein and microelement grain content, resistance to many biotic and abiotic factors. Particular interest in these species is also determined by their close relationship with Triticum aestivum L., which facilitates interspecific hybridization. The objective of this work was to analyze the nature of alien introgressions in hybrid lines from crossing common wheat varieties with T. dicoccoides and T. dicoccum, and to assess the effect of their genome fragments on the cytological stability of introgression lines. A C-banding technique and genotyping with SNP and SSR markers were used to determine localization and length of introgression fragments. Assessment of cytological stability was carried out on the basis of chromosome behavior in microsporogenesis. A molecular cytogenetic analysis of introgression wheat lines indicated that the inclusion of the genetic material of wild and domesticated emmer was carried out mainly in the form of whole arms or large fragments in the chromosomes of the B genome and less extended inserts in the A genome. At the same time, the highest frequency of introgressions of the emmer genome was observed in chromosomes 1A, 1B, 2B, and 3B. The analysis of the final stage of meiosis showed a high level of cytological stability in the vast majority of introgression wheat lines (meiotic index was 83.0–99.0 %), which ensures the formation of functional gametes in an amount sufficient for successful reproduction. These lines are of interest for the selection of promising material with agronomically valuable traits and their subsequent inclusion in the breeding process.